2015
DOI: 10.1016/j.cell.2015.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Identification of Factors for Provirus Silencing in Embryonic Stem Cells

Abstract: SUMMARY Embryonic stem cells (ESCs) repress the expression of exogenous proviruses and endogenous retroviruses (ERVs). Here, we systematically dissected the cellular factors involved in provirus repression in embryonic carcinomas (ECs) and ESCs by a genome-wide siRNA screen. Histone chaperones (Chaf1a/b), sumoylation factors (Sumo2/Ube2i/Sae1/Uba2/Senp6), and chromatin modifiers (Trim28/Eset/At-f7ip) are key determinants that establish provirus silencing. RNA-seq analysis uncovered the roles of Chaf1a/b and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
205
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(232 citation statements)
references
References 58 publications
26
205
1
Order By: Relevance
“…In ES cells, silencing of IAP was dependent on ESET, but silencing of LINE-1 was dependent on the other methyltransferase Suv39h1/2 (22,24). Intriguingly, CAF-1 knockdown in ES cells resulted in efficient induction of the twocell-like state and up-regulation of MERVL, but not non-LTR retrotransposons (25,26). A genome-wide siRNA analysis revealed that CAF-1 is the major or the sole repressor of MERVL (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ES cells, silencing of IAP was dependent on ESET, but silencing of LINE-1 was dependent on the other methyltransferase Suv39h1/2 (22,24). Intriguingly, CAF-1 knockdown in ES cells resulted in efficient induction of the twocell-like state and up-regulation of MERVL, but not non-LTR retrotransposons (25,26). A genome-wide siRNA analysis revealed that CAF-1 is the major or the sole repressor of MERVL (26).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, CAF-1 knockdown in ES cells resulted in efficient induction of the twocell-like state and up-regulation of MERVL, but not non-LTR retrotransposons (25,26). A genome-wide siRNA analysis revealed that CAF-1 is the major or the sole repressor of MERVL (26). Thus, it is likely that CAF-1 differentially represses retrotransposons in ES cells and preimplantation embryos.…”
Section: Discussionmentioning
confidence: 99%
“…The HP1 CD binds to H3K9me3. (3) The PHD domain of KAP1 is an E3 ligase that co-operates with UBE2i to sumoylate the KAP1 bromodomain (Ivanov et al 2007;Yang et al 2015). (4) The sumoylated bromodomain is bound by the NuRD complex that deacetylates acetylated histones (green circle) in preparation for histone methylation (Schultz et al 2001).…”
Section: Characterization Of Hp1-containing Heterochromatinlike Complmentioning
confidence: 99%
“…Sumoylation is mediated intra-molecularly. The KAP1 PHD domain is an E3 ligase that cooperates with UBE2i (also known as UBC9) to transfer SUMO2 (Yang et al 2015) to the KAP1 bromodomain ( Figure 3).…”
Section: Characterization Of Hp1-containing Heterochromatinlike Complmentioning
confidence: 99%
“…37 Apart from methylation, it has been recently shown that events of deacetylation and sumoylation are crucial in silencing the ERVs in embryonic stem (ES) cells. 39 Yang et al 39 through a genome wide screen of mouse ES cells have shown the role of histone chaperons Chaf1a and Chaf1b and sumoylation factors like Sumo2, Ubei 2 and few others in Trim-28-mediated proviral silencing (Fig. 4).…”
Section: Proviral Silencing Machinery In Embryonic Stem Cellsmentioning
confidence: 99%